SYNERGISTIC ANTI-CANCER EFFECTS OF NATURAL PRODUCTS AND THEIR MODE OF ACTION - GUPTA, MONIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Cancer has emerged as the second leading cause of death globally. There has been a lot of interest in other treatments like this. This includes hormonal supplements, radiation therapy, chemotherapy, surgery, and other medicines which are used in singles or combinations. Therefore, due to the habit of patient combination therapy, interactions of other drugs like hormonal supplements may be of great risk. Without consulting the doctor, the administration of herbal medicines by patients is growing rapidly in the whole world. There is also a possibility of herbal medicines. Extracts or herbal medicines are a combination of active ingredients that automatically interacts with other medicines to increase or reduce the therapeutic effect. This review focuses on the interactions of herbal medicines as well as on different types of nanoparticles (NPs), which are affected by various types of cancer treatment. Dietetic phytochemicals such as genestin, curcumin, epiglottits gillette, quercetin, and resveratrol have been given special emphasis on their working mechanism. All phytochemicals increase their therapeutic effects either by increasing the bio-availability of other drugs or by stabilizing some other medicines in the system.